Impact of recycled coal bottom ash as mixing ingredient on fresh and mechanical properties of concrete : A review - Al Biajawi, Mohammad I.; Rahimah, Embong; Kusbiantoro, Andri; Abdel-Jabbar, Haneen; Adli Hilmi, Azmi (Elsevier Ltd, 2023)
The expanding use of concrete in the global construction sector requires the exploitation of more main ingredients from nature, such as limestone, stone, sand, and rocks, which leads to an additional degradation of the state of the environment. Recognizing that this approach has negative impacts on plants, animals, and humans, a technique to use industrial byproducts as partial substitutes for concrete mix ingredients would reduce consumption of key resources and make the environment more sustainable. As a result, the huge amounts of coal bottom ash (CBA) produced annually in thermal power plants and their improper management have led to major ecological problems, as the waste has negative effects on the environment and human welfare. This review summarizes the results to date on the use of CBA as an alternative to sand and cement in concrete production. This review also examines the effects of CBA on fresh concrete properties and the mechanical properties of concrete. This paper is intended to help newcomers understand the scope and development of the use of CBA as a mix ingredient in the production of concrete. Overall, the use of CBA in appropriate proportions can improve the fresh and mechanical properties of concrete at replacement ratio up to 30% in the mechanical properties. However, further research is needed to investigate the possibility of using CBA in large quantities to achieve high-performance and durable concrete. Therefore, the inclusion of CBA as a mix ingredient in concrete production is the most effective way to reduce dependence on key ingredients and potentially minimize the negative environmental impacts caused by landfills.